Eksplorasi Metode Qirā'atul Khabar dalam Meningkatkan Kosakata Siswa Sekolah Menengan Atas Islam - Isnol Khotimah; Azmiyatun Nabihah; Nur Asiah Jamilah (JICALLS: Journal of Arabic Education, Linguistics, and Literature Studies, 2025)
The Qirā’ah method in Arabic language learning at MA Mambaul Ulum Sukodadi Paiton, Probolinggo, is implemented through Qirā’atul Khabar using varied reading texts according to students' interests. This research employs a descriptive method with a qualitative approach and is based on the assumption that students' understanding, especially in reading news texts, is not yet optimal. The research results show that students can read aloud with correct pronunciation and intonation. They can also understand the sentences in the text and their meanings well. Various topics such as Education, Inspirational Figures, and Local Wisdom keep students interested and not bored learning Arabic. This research suggests that in the future, the Qirā’ah method through Qirā’atul Khabar should be developed with more interactive and technology-based teaching materials. The use of digital media or learning applications is expected to improve student participation and create a more interesting and relevant learning experience.